EVALUASI KEGIATAN PENDAMPINGAN LITERASI DIGITAL “HOAKS” PADA KELOMPOK PENGAJIAN PEREMPUAN - Alfianistiawati, Rohmatin; Herjati Putra Dionchi, Pramana; Bararah, Hasna; Noer Fatanti, Megasari (Universitas Negeri Malang, 2022)
EVALUATION OF “HOAX” DIGITAL LITERATURE ASSISTANCEACTIVITIES IN WOMEN'S RECITATION GROUP The increasing circulation of false/hoax information amid the increasing number of internet users in Indonesia is why understanding media literacy, especially digital information, needs to be given to all levels of society, including housewives (IRT), who are often actors who spread hoaxes and affected victims. This article discusses efforts to increase the understanding of the study group about